Optimization of phosphoric acid activation on palm shell activated carbon for bio-battery - Ida Febriana; Safril Kartika Wardana; Tri Larasati; Berlian Tiaraa; Adha Triwibowo; Arief Fauzana; Lirantika; Trisnaliani, Lety (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2026)
The increasing global energy crisis and environmental issues arising from conventional battery waste have stimulated the exploration of sustainable and eco-friendly energy storage systems such as bio-batteries. This research investigated the influence of phosphoric acid (H3PO4) concentration on the characteristics of activated carbon produced from palm shell biomass and its performance in a bio-battery system. Palm shells were carbonized at 500oC and chemically activated using H3PO4 solutions with concentrations of 1 M, 1.5 M, 2 M, 2.5 M and 3 M in a mass-to-volume ratio of 1:2. The resulting activated carbon was employed as a solid-static electrolyte in a bio-battery with aluminum as the anode and copper as the cathode. The battery performance was evaluated under a constant load using a 2-volt LED, measuring voltage, current, power output and capacity. The results indicated that increasing the H3PO4 concentration improved the iodine adsorption capacity, surface porosity (based on SEM analysis), and electrochemical behavior of the bio-battery. The optimum results were achieved at 3 M H3PO4, producing an iodine adsorptiion capacity of 888.3 mg/g, a maximum voltage of 3.66 V, and a power output of 9.835 mW. It was concluded that 3 M H3PO4 yielded activated carbon with optimal physicochemical properties for bio-battery applications, supporting the development of renewable and environmentally friendly energy technologies.